2021
DOI: 10.3390/cancers13164125
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Receptor CD36 Functions as a Surrogate Parameter for Lymph Node Metastasis in Oral Squamous Cell Carcinoma

Abstract: Purpose: To investigate the expression pattern of CD36 in a patient population with oral squamous cell carcinoma (OSCC) and to correlate CD36 expression with clinical and histopathological parameters. The hypothesis was that CD36 expression correlates with the occurrence of lymph node metastasis. Methods: To address the study objectives, a retrospective cohort study was conducted. Study variables included demographic, histopathological and survival data. CD36 expression patterns were assessed by immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Other risk factors for occult metastases are histopathological parameters such as lymphovascular invasion [ 15 ] and histopathological grading [ 16 ]. Furthermore, several gene and marker expression patterns have already been studied as risk factors for occult metastases [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other risk factors for occult metastases are histopathological parameters such as lymphovascular invasion [ 15 ] and histopathological grading [ 16 ]. Furthermore, several gene and marker expression patterns have already been studied as risk factors for occult metastases [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective cohort study with primary diagnosed OSCC, patients with high CD36 expression displayed lower probability of progression-free survival, with only 34% of them alive or recurrence-free at 60 months. The study also demonstrated a 45-fold increased risk of lymph node metastasis in the CD36-high group ( Haidari et al, 2021 ).…”
Section: Cd36 In Specific Cancer Typesmentioning
confidence: 67%
“…In several types of cancer, there is a positive correlation between tumor CD36 expression and poor clinical outcome ( Abd El-Aziz et al, 2013 ; Hale et al, 2014 ; Deng et al, 2019 ; Luanpitpong et al, 2019 ; Haidari et al, 2021 ; Jeong et al, 2021 ; Luo et al, 2021 ; Yang et al, 2021 ; Pardo et al, 2022 ). Mechanistically, CD36 participates in tumor development by favoring the lipid intake in cancer cells and promoting a switch in lipid metabolism to settle the increasing energetic demand of the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study included 83 patients (female n = 33, male n = 50; with a mean age of 61 ± 15 years) diagnosed with primary oral squamous cell carcinoma (OSCC). This cohort has already been investigated in another study regarding the expression of CD36 20 . The tumor was mostly localized in the alveolar process of the mandible ( n = 29/83, 34.9%), followed by the floor of the mouth ( n = 19/83; 22,9%) and then the anterior 2/3 of the tongue ( n = 15/83; 18.1%), the hard palate and soft palate ( n = 8/83; 9.6%), and finally, the alveolar process of the maxilla ( n = 12/83; 14.5%).…”
Section: Resultsmentioning
confidence: 99%